Nutrient status of wheat growing soils in Saharanpur district of Uttar Pradesh - ., ASHOK; PRAKASH, SATYA; KUMAR, VIKAS; SHAHI, B. P. (Journal of Soil and Water Conservation, 2017)
A study was conducted on nutrient status of wheat growing soils in district Saharanpur of Uttar Pradesh. The study was conducted in Krishi Vigyan Kendra Saharanpur soil testing lab and soils from farmers field were collected in the year 2014-15 and 2015-16. Analysis results of soil samples revealed that most of the soils of Saharanpur district are low to medium in organic carbon (0.50 %), low in available nitrogen (193 kg/ha), medium in available phosphorus (11.79 kg/ha), and Potash (154.13 kg/ha), and there is a need for a close monitoring of nutrient management and application of the fertilizer recommendations on the basis of STB (soil testing based) to enhance the wheat productivity.